Formulation of thickening emulsifiers for creams and lotions in cosmetic application - Yusoff, Muhammad Faris (2016)
Thickening emulsifiers contain the combination of surfactants and polymeric thickener were formulated. The combination prepared were Carbopol 940 with Cremophor EL and Carbopol 940 with Cremophor RH. The thickening emulsifiers were than used to prepare creams using olive oil and virgin coconut oil as the model oil phase. The creams were then tested for their physical characteristics including droplet size distribution, rheological properties and texture analysis. Stability study using LUMiFuge stability analyser was also performed. Both thickening emulsifier were able to produce a good cream with a good characteristic. However, Cremophor RH thickening emulsifier had shown superiority in rheological properties, droplet size and texture compared to Cremophor EL.